Development of Tenebrio molitor (Coleoptera: Tenebrionidae) on Poultry Litter-Based Diets: Effect on Chemical Composition of Larvae - Silva, Luciana Barboza; Souza, Reneton Gomes de; Silva, Sandra Ribeiro da; Feitosa, Alisson da Costa; Lopes, Elainy Cristina; Pinheiro Lima, Stelio Bezerra; Barros Dourado, Leilane Rocha; Pavan, Bruno Ettore [UNESP] (Oxford Univ Press Inc, 2021)
In order to investigate a low-cost and sustainable food source, the present study evaluated the use of poultry litter for rearing Tenebrio molitor Linnaeus, 1758 (Coleoptera: Tenebrionidae). The experiment was performed with five diets containing increasing levels of poultry litter (0, 25, 50, 75, and 100%) replacing the control diet and five replicates with 50 larvae per sample unit. Larval growth and development were evaluated and the chemical compositions of diet and T. molitor larvae were determined. Larval development and reproduction efficiency of T. molitorwere similar in all treatments.The sole use of poultry litter to feed T. molitor reduced the crude protein of flour by only 8%. Including 50% or more poultry litter in the standard diet is the best-suited formulation for larvae production and incorporation of minerals in the larvae. Mealworm can be grown successfully on diets composed by poultry litter, the diet did not affect survival, growth, and development; however, studies spanning several insect generations should be performed to determine the effects of diet composition on adult fecundity. The knowledge acquired using poultry litter to feed T. molitor will be useful to carry out new research, in addition to evidencing the possibility of low-cost mass rearing of these larvae.
Keywords: larval growth; mealworm; protein source; nutrition; organic waste